Seleção, avaliação e utilização de uma levedura personalizada para a produção de etanol - Vicente, Fernando Antônio da Costa Figueiredo [UNESP] (2015)
Ethanol production in Brazil is based on fed-batch fermentations in large volume tanks (250,000 to 3,000,000 liters), with fast fermentations (6-12hours) and high concentrations of yeast (8-15% w/v). However, this process is subject to contamination by wild Saccharomyces strains that may cause serious problems such as low fermentation yield, flocculation and residual sugars in the wine. The research objective was to select a Saccharomyces strain, more adapted to fermentation process of Alta Mogiana mill that might be a robust yeast, dominant and persistent in the industrial fermentation process during the harvesting season. Experiments in industrial scale were conducted at Alta Mogiana mill, located in São Joaquim da Barra region, state of São Paulo, Brazil. The main steps were: 1) monitoring the population of dominant and persistent strains by karyotyping; 2) evaluation of the fermentation performance of strains in laboratory-scale; 3) re-introducing of the selected strain in the industrial fermentation process; and, 4) evaluation of the strain performance in industrial scale. The results enabled the selection of a strain (yeast UAM) that dominated the microbiota of fermentation tanks and remained in the fermentation process during all harvesting season. This strain enabled industrial gains such as the increase of alcoholic content in wine from 8 to 10%, reduction of vinasse volumes from 11.44 to 10.23 L/L ethanol and lowering the contamination by wild Saccharomyces. Moreover, this strain provided savings of thermal energy and bagasse (15,000 ton/ harvest) and contributed to increase the industrial efficiency of sugar recovery (from 88 to 92 % of processed sugar). These results demonstrate the feasibility and benefits for Brazilian distilleries to have their own yeast strain selected among the indigenous ...